Penerapan Teknik Soft Selling dalam Pemasaran Produk di Media Sosial terhadap Peningkatan Penjualan Produk dan Brand Awerness - Akbar, Arfandi; Radiah, Radiah; Sudarwanto, Tri (Universitas Batanghari Jambi, 2025)
Soft selling is a promotional technique carried out using soft, friendly and persuasive language, without pressure or coercion on potential consumers. The goal is to build long-term relationships with consumers and create the sales experience that consumers expect. This research uses an approach with a quasi-experimental design (quasi-experimental) pre-test and post-test intervention with control group design to determine the effect of treatment in the intervention group by comparing it with the control group. The population in this study were all students majoring in class X for the 2023/2024 academic year at SMK Negeri 1 Jombang, most of whom did not understand soft selling skills. The results of research using the paired t-test showed the effect of applying soft selling techniques to increasing product sales and brand awareness between the intervention group and the control group at SMK Negeri 1 Jombang.